ANALISIS KADAR C-REACTIVE PROTEIN PADA PASIEN LANJUT USIA DENGAN KOMORBID YANG TERKONFIRMASI POSITIF COVID-19 DI RSUD PASAR REBO - Enny Khotimah; Amalia Amalia (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Coronavirus Disease 2019 (COVID-19) is a disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Severe cases of SARS-CoV-2 infection are characterized by a systemic inflammatory response in acute respiration. The inflammatory response can be checked by laboratory tests with C-Reactive Protein. The purpose of this study was to determine CRP levels in elderly patients with comorbidities who were confirmed positive for Covid-19. This type of research is descriptive quantitative with a cross-sectional design using accidental sampling technique obtained a sample of 56 patients. This research was conducted at Pasar Rebo Hospital. Based on the univariate statistical test, the frequency distribution of males was 29 people (51.8%) while women were 27 people (48.2%), the elderly group with the highest group was in the elderly group with an age range of 65-69 years as many as 22 people (39.3%), elderly patients with comorbid Hypertension dominate as many as 18 people (32.1%). The results of laboratory examinations showed an increase in levels of C-Reactive Protein which varied, this was accompanied by the condition of patients who had clinical comorbidities. Covid-19 in the elderly also worsens the symptoms and course of Covid-19, due to decreased immune function, the immune system of organs and the many clinical comorbidities that occur.